The Quest for Islamic Identity among Muslim University Students in Riau, Indonesia - Khotimah Khotimah; Imron Rosidi; Rahimah Embong (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2025)
This study investigates the dynamics of transnational Islamic identity among Muslim students in Riau, Indonesia, focusing on its two distinct yet interconnected manifestations: religious activism and socio-political engagement. This research is grounded in the socio-historical context of Islamic student movements in Indonesia, which evolved from operating discreetly under the authoritarian New Order to becoming more visible and diverse in the post-Reformasi Era. This study explores how transnational Islamic identity shapes students’ religious self-understanding in a rapidly changing social landscape. Employing qualitative methods, the research draws on in-depth interviews and participant observations conducted at three major universities in Riau: Sultan Syarif Kasim State Islamic University (UIN Suska), University of Riau (UNRI), and Islamic University of Riau (UIR). The findings reveal that students negotiate their Islamic identities through engagement with transnational Islamic networks and adaptation to local cultural contexts. This negotiation reflects not a binary opposition between radicalism and moderation but a spectrum of interpretations shaped by institutional, social and global influences. This study contributes to a deeper understanding of how globalization and local sociopolitical conditions produce diverse expressions of Muslim identity in higher-education contexts. It also highlights the need for policy interventions within universities to foster critical religious literacy, intercultural dialogue, and inclusive campus environments that allow students to articulate their faith identity constructively. For future research, comparative studies across regions and institutions are recommended to examine how transnational Islamic discourses interact with local political and educational structures beyond the university settings.